2010
DOI: 10.1007/s12253-010-9276-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Romiplostim in the Treatment of Chemotherapy Induced Thrombocytopenia (CIT) in a Patient with Mantle Cell Lymphoma

Abstract: Chemotherapy induced thrombopenia (CIT) is difficult to treat, as previous treatment options, including recombinant human thrombopoietin proved to be of limited efficacy. Here we report a case of a mantle cell lymphoma patient treated with intensive chemotherapy, who belongs to Yehova's witnesses and therefore did not accept platelet transfusions. At the time of severe thrombocytopenia (zero thrombocytes/ per mikroliter) and gastrointestinal bleeding, on day 13 following the start of hyperCVAD B chemotherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…In our patient, a short course of romiplostim treatment was planned, aimed at overcoming refractoriness to immunosuppressive treatments, and to restore adequate platelet values in order to undergo splenectomy. Recently, the temporary use of romiplostim has been reported in patients with ITP associated with chronic lymphocytic leukemia, as well as to treat chemotherapy-induced thrombocytopenia in a patient unwilling to accept platelet transfusion due to religious reasons [20][21][22]. Our report confirms the efficacy of short-term romiplostim treatment, in a patient with primary ITP, with no detectable associated diseases.…”
Section: Discussionsupporting
confidence: 77%
“…In our patient, a short course of romiplostim treatment was planned, aimed at overcoming refractoriness to immunosuppressive treatments, and to restore adequate platelet values in order to undergo splenectomy. Recently, the temporary use of romiplostim has been reported in patients with ITP associated with chronic lymphocytic leukemia, as well as to treat chemotherapy-induced thrombocytopenia in a patient unwilling to accept platelet transfusion due to religious reasons [20][21][22]. Our report confirms the efficacy of short-term romiplostim treatment, in a patient with primary ITP, with no detectable associated diseases.…”
Section: Discussionsupporting
confidence: 77%
“…This rapid clinical benefit could be in part explained by the lack of accelerated peripheral PLT destruction in CIT (compared to ITP), which allows even a minimal increase of PLT production to be of clinical significance. Of note, our report goes in agreement with a similar observation reported by Demeter and colleagues 16 in a patient with mantle cell lymphoma and CIT who responded promptly to romiplostim. Indeed, this could also coincide with an early marrow recovery that facilitated the response to romiplostim.…”
Section: Discussionsupporting
confidence: 93%
“…It was recently reported that, in an patient with acute myeloid leukaemia (AML), severe immune‐mediated platelet refractoriness and symptomatic thrombocytopenia was promptly resolved by romiplostim therapy of 1 μg/kg (Berthelot‐Richer et al , ). A similar observation was reported in a chemotherapy‐treated mantle cell lymphoma patient who also responded to romiplostim (Demeter et al , ). There is concern over the stimulation of leukaemia cells via the MPL.…”
Section: Studies With Thpo‐mimetics For Other Thrombocytopenic Statessupporting
confidence: 81%